FINITE ELEMENT ANALYSIS OF POWER CABLE CONNECTION LINE FAULTS UNDER THE TIME-DOMAIN REFLECTION METHOD - Tao, Yuning (3C tecnología, 2024)
In this paper, finite element analysis of power cable connection line faults based on the time-domain reflection (TDR) method is designed to improve the accuracy and efficiency of fault detection. In terms of methodology, a distributed parameter model is used to describe the cable, and based on the fluctuation equation and characteristic impedance theory, the impedance characteristics under different fault types are analyzed. In terms of results, the effectiveness of the method is verified by mathematical modeling and simulation of single-phase ground faults and disconnection faults through the Simulink platform in MATLAB. The simulation results show that in terms of fault localization accuracy, our method controls the error within 0.07m, which is significantly improved compared with the traditional method. In addition, the fault detection under different noise signals is analyzed, which further establishes the accuracy of the TDR method in judging different fault types. The TDRbased power cable fault detection method proposed in this study not only improves the accuracy of fault localization, but also provides a reliable theoretical basis for the identification of different types of faults, which contributes to the stable operation and maintenance of power systems.